Interception of PAR and RUE of irrigated sweet potato (Ipomea batatas L.) grown in a temperate climate - Searle B; Shaw S; Sorensen I; Kerckhoffs LHJ (My University)
Searle, B., S. Shaw, I. Sorensen and L.H.J. Kerckhoffs (2014). . Poster presentation at the (Brisbane, 17-22 August 2014). [EE4]